FACTORS ON NON-PERFORMING FINANCING OF SMES AT BPRS IN INDONESIA - Choirul Anwar; Lili Puspita Sari; Hotman Hotman (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2025)
NPF in the largest Islamic banking occurs in BPRS institutions compared to BUS and UUS. The highest NPF in the financing category of BPRS comes from the SME category compared to non-SMEs. This research aims to identify the external and internal factors affecting the NPF of SMEs in BPRS. This study uses a quantitative approach with the ARDL method. The data used is quarterly secondary data from 2015-2023. In the short term, all variables have varying effects on the NPF of the SME category at lags 1 to 4. Furthermore, in the long term, inflation and ROA have a significant positive effect on the NPF of the SME category. Conversely, the exchange rate and FDR have a significant negative effect on the NPF of the SME category.